Le Comte Henry Russell dans son « jardin » - Gilles Duval (Caliban: French Journal of English Studies, 2018)
Russell (1834-1909) was arguably the greatest explorer of the Pyrenees ever. He was well aware that the mountain is not just a matter of vast spaces. So in many ways he cultivated his own garden, a spot in the all-encompassing universe. Even now he prompts us to question current toponymy, for example concerning the location of the « jardin anglais » in the Ossau massif. In the wake of his model Ramond, his observations of minute insects in moments of stress and danger are specially striking and convincing. And his controversial artificial grottos close to the summit of Vignemale can be seen as one more instance of his obsession with Robinson’s domestication of nature.